Parametric study of a novel vibro-impact energy harvesting system with dielectric elastomer. (15th December 2017) - Yurchenko, D.; Lai, Z.H.; Thomson, G.; Val, D.V.; Bobryk, R.V.
Highlights: Novel vibro-impact energy harvesting system with dielectric elastomers is proposed. Complex dynamics of the device is studied under an external harmonic excitation. Output energy depends on an inclination angle of the device and initial conditions. Presented results can be used to optimize the device design and inclination angle. Abstract: A vibro-impacting mechanical system with two dielectric elastomeric membranes for harvesting energy from ambient vibrations is proposed. The purpose of the paper is to study the system performance under different angles of its inclination with respect to a horizontal position in the effort to determine the best layout of the system. The dimensional, electrical and dynamic parameters of the dielectric elastomeric membrane are analysed and then used to numerically estimate the output voltage of the proposed system. The electrical properties of the dielectric elastomer membrane are validated experimentally, and the dynamic behaviors of the system are fully studied under different initial conditions. The system output performances under harmonic excitation are further discussed. The approach and an application example for the design of the proposed device subjected to a certain vibrational environment is presented.